Biotransformation of phenol using immobilized polyphenol oxidase from banana stem - Azhari, Anuar (2010)
Polyphenol oxidase(PPO) is an enzyme that can easily find in most of the plants.It is a browning agent that cause from catalyzing the oxidation of various phenolic compounds to the corresponding quinones which lead to the formation of melanin pigment.PPO commonly used as biocatalyst in a biotransformation reaction and in this study is converting phenol to less harmful compound.The objective of this study was to study the basic kinetics of batch and continuous reactors.By conducting biotransformation using polyphenol oxidase extracted from banana stem.The enzyme immobilized using Ca-Alginate in the forms of beads.Five different phenol concentrations were transformed using different enzyme loadings for batch mode while different flow rates were used in continuous mode.Samples were analyzed using High Performance Liquid Chromatography(HPLC)at 254nm,using methanol and water (20:80) as mobile phase at 1mL/min.The space time of a batch reactor was determined and weight of catalyst loading was estimated for continuous reactor.